A New High‐Performance Proton‐Conducting Electrolyte for Next‐Generation Solid Oxide Fuel Cells. Issue 9 (24th July 2020) - Radenahmad, Nikdalila; Afif, Ahmed; Abdalla, Abdalla M.; Saqib, Muhammad; Park, Jun-Young; Zaini, Juliana; Irvine, John; Kim, Jung Hyun; Azad, Abul K.
Abstract : Conventional solid oxide fuel cells (SOFCs) are operable at high temperatures (700–1000 °C) with the most commonly used electrolyte, yttria‐stabilized zirconia (YSZ). SOFC research and development activities have thus been carried out to reduce the SOFC operating temperature. At intermediate temperatures (400–700 °C), barium cerate (BaCeO3 ) and barium zirconate (BaZrO3 ) are good candidates for use as proton‐conducting electrolytes due to their promising electrochemical characteristics. Herein, two widely studied proton‐conducting materials with two dopants are combined and an attractive composition for the investigation of electrochemical behaviors is discovered. Ba0.9 Sr0.1 Ce0.5 Zr0.35 Y0.1 Sm0.05 O3− δ (BSCZYSm), a perovskite‐type polycrystalline material, has shown very promising properties to be used as proton‐conducting electrolyte at intermediate temperature range. BSCZYSm shows a high proton conductivity of 4.167 × 10 −3 S cm −1 in a wet argon atmosphere and peak power density of 581.7 mW cm −2 in Ni–BSCZYSm | BSCZYSm | BSCF cell arrangement at 700 °C, which is one of the highest in comparison with proton‐conducting electrolyte‐based fuel cells reported until now. Abstract : Intermediate‐temperature solid oxide fuel cells (IT‐SOFCs) operate in the range 400–700 °C. Ba0.9 Sr0.1 Ce0.5 Zr0.35 Y0.1 Sm0.05 O3− δ (BSCZYSm), a proton‐conducting perovskite‐type polycrystalline material, shows a peak power density of 581.7 mW cm −2 in Ni–BSCZYSm | BSCZYSm | BSCF cell arrangement at 700 °C which is one of the highest performances in comparison with other proton‐conducting electrolyte‐based IT‐SOFCs reported till now.